The Library Staff Development Handbook: How to Maximize Your Library’s Most Important Resource - Flaherty, Mary Grace (Rowman & Littlefield Publishers, 2017)
The Library Staff Development Handbook: How to Maximize Your Library’s Most Important Resource provides practical tips, suggestions for resources, and concrete examples for addressing the multiple and varied aspects of staff development. From crafting a job description to recruitment, hiring and retention, and from progressive discipline and succession planning to continuing education, performance appraisals, and the importance of workplace fun, this handbook can serve as a companion for managers, supervisors and library staff as they negotiate the challenging range of staffing issues and the opportunities they provide in the library setting.